A STUDY ON MINDFULNESS: THE EFFECT OF MINDFULNESS ON STRESS AND RECOVERY IN ATHLETES USING BIBLIOMETRIC ANALYSIS - Putra, Handhika Surya; Bintari, Dini Rahma (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2024)
There is limited comprehensive understanding of the development of research in the field of mindfulness for athletes. This bibliometric analysis plays a role in directing future research. This study is specifically to review the effect of mindfulness on stress and recovery in athletes published from the Scopus database by using bibliometric analysis to see the publication of mindfulness in its annual development, the most citations of articles, journals that are productive in discussing this topic, keywords that appear on this topic and emerging themes related to mindfulness in athletes. The extracted data were analyzed and visualized using VOSviewer, RStudio and Scopus. A total of 124 articles focusing on mindfulness for stress and recovery in athletes were identified in the title, abstract and keywords. This analysis showed a rapid increase from 2019 to 2024 which recorded 90 published articles discussing the influence of mindfulness on athletes. Studies on the effect of mindfulness on stress and recovery in athletes also show that it is not limited to athletes only but also to public health who exercise or do not exercise. This indicates that mindfulness can be applied to a variety of individual and societal conditions whether they are active as athletes or non-athletes.